ECONOMIC JUSTIFICATION OF THE CALCULATION OF THE COSTS OF DEFENSE OF DOCTOR OF PHILOSOPHY THESES (USING THE EXAMPLE OF OLES HONCHAR DNIPRO NATIONAL UNIVERSITY) - Vainilovych, Iryna (Social Economics, 2025)
The article presents an economic justification for the cost of organizing and conducting the defense of theses of PhD candidates who did not complete a full course of study within the educational and scientific program of a higher education institution. A comparative analysis of regulatory and legal support and financial mechanisms in Ukraine and abroad was conducted. It was found that for a higher education institution, the process of organizing and conducting a defense is associated with additional financial costs, since it includes financing the maintenance of information, library, and material and technical resources, payment for utilities and other services, checking dissertations for plagiarism, issuing diplomas, and also requires the involvement of official opponents and ensuring the work of technical and administrative personnel. In international practice, two models are distinguished: if the applicant is not currently studying under the educational and scientific program, the institution or the state charges him a special fee, or covers all costs for certification procedures through budget financing or inclusion in the cost of the applicant’s third (educational and scientific) level of higher education. Using the example of Oles Honchar Dnipro National University, an economic model of cost calculation was developed, taking into account direct and indirect costs associated with the certification procedure and defense of a PhD thesis by applicants who are not graduates of the educational and scientific program of this particular higher education institution. A transparent approach to establishing the cost of paid services for organizing defense for third-party applicants of the third (educational and scientific) level of higher education is proposed, which ensures the financial stability of the higher education institution, the integrity and openness of the procedure for attestation and defense of the Doctor of Philosophy dissertation.